Drawing Sound as Landscape - David Buck (Opticon1826, 2014)
This essay discusses the relationship between music notation, sound, and landscape. I explore how the notation of musical sounds might lead to new methods for drawing auditory landscapes. There are three components to the research: an analysis of the score of English composer Michael Finnissy’s composition Green Meadows (1977); a reference to ethnomusicology to explore how the notation of sound-as-music might allow us to draw sound-as-landscape; and a notation to investigate the composition of a landscape through sound. In conclusion, I question how auditory landscapes might be composed, and suggest ways in which both drawing and sound might be considered landscape.
Keywords: notation; landscape